Crop domestication disrupts intercropping benefits: A case study from barley–faba bean mixture under contrasting P inputs - Tang, Xiaoyan; Wu, Zhengwu; Hu, Siliu; Chen, Guangdeng; Huang, Rong; Wu, Yingjie; Li, Bing; Tao, Qi; Jin, Kemo; Wang, Changquan; Wen, Zhihui (Frontiers in Plant Science, 2023)
How crop domestication mediates root functional traits and trait plasticity in response to neighboring plants is unclear, but it is important for selecting potential species to be grown together to facilitate P uptake. We grew two barley accessions representing a two-stage domestication process as alone or mixed with faba bean under low and high P inputs. We analyzed six root functional traits associated with P acquisition and plant P uptake in five cropping treatments in two pot experiments. The spatial and temporal pattern of root acid phosphatase activity was characterized in situ with zymography at 7, 14, 21 and 28 days after sowing in rhizobox. Under low P supply, wild barley had higher total root length (TRL), specific root length (SRL) and root branching intensity (RootBr) and the activity of acid phosphatase activity (APase) in the rhizosphere, but lower root exudation of carboxylates and mycorrhizal colonization (MC), relative to domesticated barley. In response to neighboring faba bean, wild barley exhibited larger plasticity in all root morphological traits (TRL, SRL and RootBr), while domesticated barley showed greater plasticity in root exudates of carboxylates and colonization by mycorrhiza. Wild barley with greater root morphology-related traits plasticity was a better match with faba bean than domesticated barley, indicated by higher P uptake benefits in wild barley/faba bean than domesticated barley/faba bean mixtures under low P supply. Our findings indicated that domestication of barley disrupts the intercropping benefits with faba bean through the shifts of root morphological traits and their plasticity in barley. Such findings provide valuable information for barley genotype breeding and the selection of species combinations to enhance P uptake.